Achieving sustainable agricultural practices: From incentives to adoption and outcomes - Piñeiro, Valeria; Arias, Joaquin; Elverdin, Pablo; Ibáñez, Ana María; Morales Opazo, Cristian; Prager, Steven D.; Torero, Máximo (International Food Policy Research Institute, 2021)
Sustainable agricultural practices enable more efficient use of natural resources, mitigate the impact of agriculture on the environment, and strengthen capacity for adaptation to climate change and climate variability. Because these practices usually require substantial effort or resource allocation from farmers, incentives are necessary to support farmer adoption. Despite growing interest, there has been little systematic evaluation of the incentives–adoption–outcome chain—that is, which incentives best promote adoption and which lead to desired sustainability outcomes. This brief presents the results of a literature review that examined (1) uptake agricultural practices under three kinds of incentives, market and nonmarket, regulations, and cross-compliance, and (2) the impact on productivity, profitability, and environmental sustainability. Based on this review, it offers a set of seven tested principles to follow in designing and implementing incentives for sustainable agriculture.